(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article highlights the issues of ensuring the surface strength of the cement concrete pavement of roads. Increasing requirements for reliability, performance and strength of pavements are caused by an increase in the carrying capacity of vehicles and the intensity of traffic on the roads